Epidemiology of pelvic fracture in the emergency room at Dr. Soetomo General Hospital between 2016-2018 - Yuga Ramadana; M Zaim Chilmi (Universitas Muhammadiyah Surabaya, 2022)
ABSTRACT Pelvic fracture is a rare case. The incidence is about 3% to 8% of the whole kind of fractures. The most common cause is high energy trauma and is associated with multi-trauma. The amount of pelvic trauma patients is 63,000 and is associated with increased mortality rates. The scientific data is needed because it is helpful for trauma prevention and management. This research is a descriptive observational study that examines the epidemiology of pelvic trauma. The population was patients with pelvic trauma who came to the ER RSUD Dr. Soetomo in 2016-2018. The total sample was 229 patients. A total of 149 patients (65.1%) were male, and 80 patients (34.9%) were female. Traffic accidents caused 173 patients (76%) cases. Tile A classification was most frequent in 117 patients (51.1%). There were 178 patients (77.7%) who were multi-trauma patients. The most common treatment was pelvic bandage with 95 patients (41.5%). There were 178 multi-trauma patients, 109 patients (61.2%) who underwent emergency surgery for trauma, and 69 patients (38.8%) who did not. The most common cause of pelvic fracture in Dr. Soetomo general hospital during 2016-2018 was trauma with high energy due to traffic accidents. The most common type of pelvic fracture was Tile A. The more severe the pelvic trauma, the treatment should be more aggressive.